Research progress on molecular mechanisms of hepatocellular carcinoma induced by heavy metal cadmium exposure - An Hongmei; Hu Shuaiyue; Chen Jiongfei; Ying Shibo (生物医学转化)
Cadmium is a common and highly toxic environmental heavy metal that has been shown to be closely associated with various human diseases, particularly hepatocellular carcinoma (HCC). In recent years, with the worsening of environmental pollution and growing public concern over the health effects of heavy metals, the carcinogenic mechanisms of cadmium have become a major focus of research. Studies have shown that cadmium can affect hepatocytes through several biological pathways, including oxidative stress, inflammatory responses, and gene expression regulation, thereby promoting the development of HCC. However, the exact molecular mechanisms underlying cadmium-induced hepatocarcinogenesis have not yet been fully elucidated. This review summarizes recent findings on the impact of cadmium exposure on hepatocytes and its role in carcinogenesis, examines how cadmium contributes to HCC development through different biological pathways, and analyzes its oncogenic effects, with the aim of providing a scientific foundation for future preventive and therapeutic strategies.